Selective attention of elite versus youth biathletes in rest and after physical load - Birklbauer, J.; Dirnberger, J.; Buchecker, M.; Sattlecker, G.; Finkenzeller, T.; Kösters, A.; Wiesinger, H.-P. (29th Annual Congress of the European College of Sport Science (ECSS), 2024)
INTRODUCTION: Attention abilities are critically important for performance in self-paced and far-aiming sports, enabling athletes to focus on targets and resist distractions. Accordingly, elites in shooting and archery showed better selective attention compared to their lower-level counterparts (1). In biathlon, demands on attention are arguably even greater, as shooting has to be completed under time constraints and significant physical exertion. First indications of enhanced conflict control in biathletes with superior shooting performance were derived from cluster analyses (2). Based on these preliminary findings, we hypothesized that elite outperform youth biathletes in visual interference control of attention during rest and even more after physical exertion.